Tissue culture (Micropropagation) of Dalbergia sissoo Roxb. as affected by Genotypic configuration - Bakshi, Meena; Chauhan, Aradhna; Vichitra, Ankur (Indian Forester, 2018)
Genotypic variation in in-vitro performance of 5clones of Dalbergia sissoo revealed significant variations in bud proliferation and multiplication. The survival percentage of explants inoculated on MS medium with 1.0 mg/l BAP+ 0.1 mg/l NAA ranged from 56.9 to 79.1 % with the maximum being in C14 (Haridwar). Maximum bud break (69.4%) was found in C 114 (Nepal) while number of buds was maximum (2.79) in C86. The shoot number and length were maximum (1.65 and 2.05cm respectively) in C14. Subculturing of microshoots on 1.0 mg/l BAP+ 0.25 mg/l NAA revealed maximum multiplication rate of 4.02 in C14 with maximum shoot number (3.07) while shoot length was maximum (2.43 cm) in C 86. The maximum rooting (40.5%) with 1mg/l IBA was observed in C86 (Rajasthan) at par with C14 (40%). Significantly (0.1%) maximum number of roots (2.46) and root length (2.63 cm) were also recorded in C14 with high survival rate. Among 5 selected clones, C14 (Haridwar) showed best performance in shooting as well as rooting in vitro, hence can be multiplied reliably to be put under agro-forestry plantations.